Quality improvement interventions to prevent neonatal necrotizing enterocolitis: a systematic review - Zhang, Xueli; Chen, Mingqiu; Zhang, Yanfei; Zhou, Jieer; Wei, Tingyan; Yu, Zhangbin; Yan, Yuqin; Wang, Zhangxing (Frontiers in Pediatrics, 2025)
BackgroundNeonatal necrotizing enterocolitis (NEC) is the leading cause of death due to gastrointestinal disease in preterm neonates. Quality improvement bundles could reduce the incidence of NEC in preterm infants, but their replication in neonatal intensive care units has had inconsistent outcomes.ObjectiveQuality improvement may reduce the incidence and severity of NEC in preterm infants. We evaluated quality improvement interventions (QIIs) that sought to prevent or reduce the severity of NEC.MethodsPubMed, Embase, Cochrane Library, Web of Science, Wanfang Database, China National Knowledge Infrastructure (CNKI), VIP Chinese Journal Service Platform (VIP), Chinese BioMedical Literature Database (CBM), and citations of selected articles were searched. QIIs that reduced the incidence or severity of NEC in preterm infants were the primary outcome. Paired reviewers independently extracted data from selected studies.ResultsIn total, 13 quality improvement interventions involving 17,961 infants were included. Nearly all of the QIIs included improving breastfeeding rates. Moreover, 16 of the 19 QIIs resulted in a significant reduction in the incidence of NEC after their implementation. Application of the quality criteria of the quality improvement showed that all the interventions were considered to be of medium to high quality, with the lowest score being 8 and 13 of the interventions having scores more than 10. The studies had heterogeneity with significant variations in intervention characteristics, implementation units, personnel, sample size, time, and outcomes.ConclusionQIIs resulted in reductions in the incidence and severity of NEC in preterm infants in some but not all settings. The specific interventions and quality improvement methods that were responsible for those reductions and why they were successful in some settings but not others are unclear. This systematic review can assist teams in identifying potentially better practices for reducing NEC. Systematic Reviews Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024601939, PROSPERO (CRD42024601939).